Functional proteins in breast milk and their correlation with the development of the infant gut microbiota: a study of mother-infant pairs - Xi, Menglu; Liang, Dong; Yan, Yalu; Duan, Sufang; Leng, Houxi; Yang, Haibing; Shi, Xiaojin; Na, Xiaona; Yang, Yucheng; Yang, Celi; Szeto, Ignatius Man-Yau; Zhao, Ai (Frontiers in Microbiology, 2023)
Proteins in breast milk play an important role in the growth and development of infants. This study aims to explore the correlation between functional proteins in breast milk and the infant gut microbiota. Twenty-three mothers and their infants were enrolled and breast milk samples and infant fecal samples were collected. Breast milk protein content was determined by UPLC-MS/MS, and 16S rRNA sequencing was employed to analyze the gut microbiota of infant. The results indicated that the secretory immunoglobulin A (sIgA) content in breast milk was positively correlated with the abundance of Veillonella parvula. The κ-casein content was positively correlated with the abundance of Clostridium butyricum. The osteopontin (OPN) and lactalbumin contents were positively correlated with the abundance of Parabacteroides distasonis at 42 days. Functional pathway analysis showed that the OPN and κ-casein contents in breast milk were significantly correlated with amino acid, pyruvate, propionic acid, linoleic acid, and alpha-linolenic acid metabolic pathways in early life. In conclusion, the results of this study suggest that specific proteins in breast milk can influence the abundance of certain gut microbes in infants, playing an important role in early immune and metabolic development.